Pelatihan Pengisian Aplikasi Pelaporan SPMI - Marice Hotnauli Simbolon; Ivan Benedict Tambunan; Lanta Siringo Ringo; Mentari Simbolon (Universitas Mandiri Bina Prestasi (UMBP), 2026)
Akademi Pariwisata dan Perhotelan Darma Agung is a higher education institution that offers two study programs with broad career prospects in the hospitality industry, namely Program Studi Perhotelan and Program Studi Usaha Perjalanan Wisata for the three-year diploma level. Regarding SPMI reporting, Akademi Pariwisata dan Perhotelan Darma Agung has not yet activated its SPMI account, thus requiring guidance and assistance in activating and completing performance reports for each department within the academy through the SPMI Reporting Application. The SPMI reporting process is mandatory for all higher education institutions under Kementerian Pendidikan Tinggi, Sains, dan Teknologi Republik Indonesia. The purpose of filling out the SPMI reporting application is to ensure that higher education institutions have implemented the PPEPP (Penetapan, Pelaksanaan, Evaluasi, Pengendalian, Peningkatan) cycle in meeting the Standar Nasional Pendidikan Tinggi (SN-Dikti), in accordance with and/or exceeding Permendikbudristek No. 53 of 2023. The reporting period for the SPMI cycle begins in March and ends in May at Akademi Pariwisata dan Perhotelan Darma Agung, after which verification is carried out by regional facilitators. Following verification by the facilitators, Akademi Pariwisata dan Perhotelan Darma Agung is given time to make updates and respond to improvement notes from regional facilitators from around August to September. Then the facilitator conducts a final verification, validation, provision of notes, recommendations for improvement, and SPMI typology assessment in November, and the SPMI Award is held in December. However, for the 2025 Performance, the SPMI Award will be held in early 2026, specifically on Tuesday, January 27, 2026. Akademi Pariwisata dan Perhotelan Darma Agung received a ranking of two in the Evaluation Category and a nomination in the Improvement Category.